The Self-Adjustment of People Who Engage in Interfaith Dating - Irine Putri Nalaria; Nurchayati Nurchayati (Character Jurnal Penelitian Psikologi, 2023)
Using the phenomenological approach, this qualitative psychological study aims to understand the self-adjustment of people who engage in interfaith dating. Data for this study was collected through interviews with three couples involved in an interfaith relationship for more than a year. The Interpretative Phenomenological Analysis (IPA) performed on the data yielded several emerging themes, including aspects of self-adjustment, supporting factors, and self-adjustment process. This study concludes that all the partners in the interfaith relationships have engaged in acts of self-adjustment to make their relationship work.